The quality of medical services in a subjective assessment of hospitalized patients using the SERVQUAL method – a pilot study - Węgłowski, Paweł; Zwolińska, Danuta; Karniej, Piotr; Nocuń-Wasilewska, Karolina; Polak-Jonkisz, Dorota (Family Medicine & Primary Care Review, 2016)
Background . The provision of medical services to patients according to their expectations and needs is necessary for the comfort and quality of life of patients, as well as for the standardization of hospital procedures. In recognizing these needs and expectations, an important step is the verification of provided services in order to improve their quality. The present study was designed to determine differences in service quality, as evaluated by hospitalized patients. Objectives . The analysis of the subjective feelings of hospitalized patients concerning service quality in the context of the application of the SER VQUAL method – a pilot study. Material and methods. The study was conducted in a Lower Silesian hospital in a group of 29 young patients (women: 16, men: 13, average age: 16) diagnosed with kidney disease. In the study a standard sheet of 22 SER VQUAL statements was used, and an analysis of the validity of 5 quality areas important for the patient was conducted. Results. According to the respondents, the most important of all 5 features directly affecting the quality of life during treatment is the ability and skill of the ward staff to provide medical services, so-called reliability – 24.48%. In turn, the least important of all the study characteristics was the aesthetics and ergonomics of rooms, the presence of appropriate equipment, the so-called material dimension – 15.31%. Furthermore, service quality gaps were visible in all five service quality dimensions. Conclusions . 1. The SER VQUAL method helps to identify discrepancies between the perceptions of patients’ expectations in all dimensions of the quality of provided medical services. 2. For the patients the least important is the material dimension, and the most affecting is the dimension associated with the reliability of the medical services. 3. Improvement of the level of satisfaction with the quality of medical services requires proper planning and effective actions while providing health care services. 4. It is recommended to conduct the study on a larger population of patients.